Sanctioning bias crime: a public perspective - Pearlman, Terrylynn (Criminal justice: recent scholarship, 2008)
Bias crime legislation and public opinion : an overview -- The emergence and legality of bias crime legislation -- Scholarly perspectives on bias crime legislation -- Public opinion research on bias crime and legislation -- Public opinion research on crime and punishment and its relevance to bias crime -- The current study : design to analysis -- Citizens : views on bias crime -- Citizens : bias crime policy preferences -- Citizens : responses to bias crime vignettes -- Citizens : views on bias crime legislation -- Findings and implications